Water, the limiting resource - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Water levels in many parts of the world are low and getting lower. Rivers have retreated from their banks, lakes are shrinking from their former shores and boreholes are pierced ever deeper to tap falling water tables. Almost universally water is...